Enhancing tumor penetration: GSH-sensitive paclitaxel liposomes modified with Dermaseptin-PP - Ziyi Dong; Qin Zhang; Qing Zhang; Wenjun Hu; Liwen Yan; Fengqi Peng; Zucheng Hu; Jakkree Tangthianchaichana; Yueying Zhao; Shouying Du; Yang Lu (Materials & Design)
The dense structure of solid tumor tissues and the selective permeability of cell membranes impede the effective penetration of chemotherapeutic agent-loaded liposomes into tumors and their subsequent uptake by cells. Dermaseptin-PP, a cationic antimicrobial peptide, has demonstrated the ability to enhance the penetration and accumulation of drugs within solid tumors due to its unique membrane-breaking action. Based on this, we designed glutathione (GSH)-sensitive paclitaxel liposomes modified with Dermaseptin-PP. Dermaseptin-PP was modified through disulfide bonding, which could be broken at the tumor site due to high GSH levels. This cleavage resulted in the release of Dermaseptin-PP, thereby enhancing the permeability of the paclitaxel liposomes within the tumor. We found that the paclitaxel liposomes modified with Dermaseptin-PP were extensively distributed to the tumor site, and the Dermaseptin-PP modification significantly enhanced liposome penetration within the tumor. Our study significantly increased the anti-tumor efficacy of paclitaxel liposomes. Our study confirms that paclitaxel liposomes modified with Dermaseptin-PP is an effective anti-tumor therapy that enhances deep penetration into tumors. Additionally, this broadens the applications of cationic antimicrobial peptides.